Islet1 Precursors Contribute to Mature Interneuron Subtypes in Mouse Neocortex. (6th July 2021) - Siddiqi, Faez; Trakimas, Alexandria L; Joseph, Donald J; Lippincott, Margaret L; Marsh, Eric D; Wolfe, John H
Abstract: Cortical interneurons (GABAergic cells) arise during embryogenesis primarily from the medial and caudal ganglionic eminences (MGE and CGE, respectively) with a small population generated from the preoptic area (POA). Progenitors from the lateral ganglionic eminence (LGE) are thought to only generate GABAergic medium spiny neurons that populate the striatum and project to the globus pallidus. Here, we report evidence that neuronal precursors that express the LGE-specific transcription factor Islet1 ( Isl1 ) can give rise to a small population of cortical interneurons. Lineage tracing and homozygous deletion of Nkx2.1 in Isl1 fate-mapped mice showed that neighboring MGE/POA-specific Nkx2.1 cells and LGE-specific Isl1 cells make both common and distinct lineal contributions towards cortical interneuron fate. Although the majority of cells had overlapping transcriptional domains between Nkx2.1 and Isl1, a population of Isl1-only derived cells also contributed to the adult cerebral cortex. The data indicate that Isl1 -derived cells may originate from both the LGE and the adjacent LGE/MGE boundary regions to generate diverse neuronal progeny. Thus, a small population of neocortical interneurons appear to originate from Isl-1-positive precursors.